KONSEP BID’AH HASANAH (Perpspektif Maqashid Al-Syathibi dan Ibnu ‘Asyur) - Zaidan Anshari (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
Bid’ah is the classic issue but stil actual to be discussed. It is caused by the classification of bid’ah term into two kinds still presents the polemic till this era. The different opinion about this concept is unsolved yet. Adherent of bid’ah hasanah and repellent of it have argument each other. Principle of their argument may comes from hadis perpective, sahabah perspective (attitude of sahabah), language perspective, and also ushul fiqh perspective. This perspective (ushul fiqh) is the most difficult instrument to understand the substance of hadis, especially the hadis which talk about bid’ah. But there is the chapter of ushul fiqh which talk about the purpose of syariah, it called by maqashid syariah. From this perspective we can try to explain the concept of bid’ah hasanah. There are two most popular theory of maqashid syariah from two figures of different period. Al-syathibi and Ibnu ‘Asyur, talk in detail of maqashid syariah. From their theory, the concept of bid’ah hasanah can result the different view. Al-Syathibi’s theory refuses explicitly the concept of bid’ah hasanah. Whereas in the Ibnu ‘Asyur’s theory of maqashid, this concept still has chances to be justified. This article will try to research this concept from these two perspectives.